“Eu vou começa a fala [...] eu sair escondido” – estratégias para trabalhar com o apagamento e a hipercorreção em sala de aula - Bomfim, Jussileide Ramos (2021)
The scope of this report is, in the light of phonetics and phonoaudiology, the study of the erasure of the letter /R/ on infinitive verbs, as well as the hypercorrelation of the /R/ on syllabic coda, in texts from elementary school II nineth grade students enrolled on urban area schools in the city of Aracaju/SE. Preliminary analysis of said texts indicate that the students erased the /R/ grapheme sometimes, and from time to time they inserted the /R/ grapheme unduly. Therefore, we raised the hypothesis that as for the erasure of the grapheme, students were leaning on the speech, thus being a direct interference of the orality over the writing; and, in the case of the of the unduly addition of the grapheme in detriment of the flexed verb, it is about the students selfovercorrecting, in his will to be right. We utilized the research-action methodology from which we quantified and interpreted the data acquired from the students texts, with the objective of identifying the frequency/occurrence of the erasure of the /R/ on the syllabic coda on infinitive verbs and hypercorrelation in verbs that should be flexed, but are in the infinitive form. Our research´s theoretical contributions comes from: Bortoni-Ricardo (2005); Callou, D. (2009); Capovilla, A.G.S. & Capovilla, F.C. (2000, 2002); Marcuschi, L.A. (1997, 2010); Seara, I.C. et al (2019); Cristófaro-Silva, T. (2017); Cristófaro-Silva et al (2019) amongst others. Based on our surveys, aiming to decrease the incidence of both erasure and improper addition of the /R/ grapheme on syllabic coda, we developed a sequence of activities, spread throughout 8 classes, using the interview method that culminated on the confection of the “Revista Colégio JVS – Histórias que ouvi; histórias que vivi; histórias que escrevi”, with texts written by the students where they tell stories about their local communities, posteriorly published on the schools social networks. By the end of the study, we resumed the analysis of the students texts produced after being exposed to the magazine, and we could verify the efficiency of the proposed solution; because, initially, we had the following data: 89% of the students texts contained cases of wrongful erasure of the /R/ grapheme on syllabic coda on infinitive verbs and/or hypercorrelation in verbs that should be in its flexed form instead of infinitive, and 11% showed none of those cases. After the application of the intervention activities those number got practically inverted, with only 15% of the texts showing cases of such processes, and none of them in the remaining 85%, testifying to the success of the proposed solution in creating phonological awareness in those regards.